2013
DOI: 10.1186/1756-0500-6-102
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of mental workload in Dutch university employees of different ages: a focus group study

Abstract: BackgroundAs academic workload seems to be increasing, many studies examined factors that contribute to the mental workload of academics. Age-related differences in work motives and intellectual ability may lead to differences in experienced workload and in the way employees experience work features. This study aims to obtain a better understanding of age differences in sources of mental workload. 33 academics from one faculty discussed causes of workload during focus group interviews, stratified by age.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
8
0
2
Order By: Relevance
“…Technological development and increased competition nationally and internationally have led to gradually higher demands on efficiency and productivity, greater demand for distance learning, and expectations of staff being available anytime (Melin et al 2014;Ng 2006;Saltmarsh 2011;Saltmarsh and Randell-Moon 2015;Sutherland-Smith 2013). It has been argued that increased focus on management and performance evaluations have contributed to the deterioration of working conditions (Kenny 2018), and studies from several countries show that academics find their work situation demanding and report high levels of work-related stress (Bos et al 2013;Kang and Sidhu 2015;Melin et al 2014;Saltmarsh and Randell-Moon 2015). Among teaching and research staff, stressors have been identified as relationships with colleagues and superiors, high workload, lack of control over work, inadequate resources, work-life imbalance, and lack of personal development (Kang and Sidhu 2015;Ng 2006;Opstrup and Pihl-Thingvad 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Technological development and increased competition nationally and internationally have led to gradually higher demands on efficiency and productivity, greater demand for distance learning, and expectations of staff being available anytime (Melin et al 2014;Ng 2006;Saltmarsh 2011;Saltmarsh and Randell-Moon 2015;Sutherland-Smith 2013). It has been argued that increased focus on management and performance evaluations have contributed to the deterioration of working conditions (Kenny 2018), and studies from several countries show that academics find their work situation demanding and report high levels of work-related stress (Bos et al 2013;Kang and Sidhu 2015;Melin et al 2014;Saltmarsh and Randell-Moon 2015). Among teaching and research staff, stressors have been identified as relationships with colleagues and superiors, high workload, lack of control over work, inadequate resources, work-life imbalance, and lack of personal development (Kang and Sidhu 2015;Ng 2006;Opstrup and Pihl-Thingvad 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals’ participation in workplace health promotion was affected by structural (quantitative and physical demands, organisation of work) and interpersonal (social support by colleagues and supervisors) factors. Dutch focus-group research among university staff showed that demands by the university, their own high working standards and the fear of having less time for research led to huge mental stress ( 20 ). Corresponding to the literature, in our study the primary workplace stress factors experienced by employees were strict deadlines (80.4%), frequent overwork (64.2%) and difficulty in meeting requirements (56.7%).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the physicians answered that he was reviewing the outpatients’ data of that day, which could have been recorded as indirect patient care. This may imply the voluntary overtime work of hospital physicians [ 1 ]. Similarly, working at home was reported in other study [ 16 ], suggesting future studies are needed to evaluate such physicians’ voluntary work more properly.…”
Section: Discussionmentioning
confidence: 99%
“…The term “triple role” or “triple duties” describes the characteristics of a physician’s work as a clinician, educator, and researcher in academic medicine [ 1 3 ]. Preparing for a lecture and obtaining grants for research, in addition to daily patient care is difficult and stressful [ 1 , 3 , 4 ]. This is also true for Japanese hospital physicians.…”
Section: Introductionmentioning
confidence: 99%